2019
DOI: 10.1108/qmr-10-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

A process view of the role of integrated marketing communications during brand crises

Abstract: Purpose This paper aims to explore the internal processes that can enable firms to identify and effectively respond to brand crises, with various groups coordinating and cooperating with each other, and also propose a guiding framework relevant for both managers and researchers. Design/methodology/approach A grounded theory methodology was adopted. Data collection included open-ended interviews with 13 executives representing the integrated marketing communications (IMC) function, the integrated corporate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 85 publications
(111 reference statements)
3
10
0
3
Order By: Relevance
“…“Information providing” and “monitoring” can help companies to follow Sense Inform Respond process, for developing their communication strategies during crisis (Hewett and Lemon, 2019). Monitoring will allow to scan (sense) the environment and gather insights, which will help to disseminate the information through coordinated messaging (Hewett and Lemon, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…“Information providing” and “monitoring” can help companies to follow Sense Inform Respond process, for developing their communication strategies during crisis (Hewett and Lemon, 2019). Monitoring will allow to scan (sense) the environment and gather insights, which will help to disseminate the information through coordinated messaging (Hewett and Lemon, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that crisis issues indicate that corporate communication during a crisis assumes strategic significance. The brand crisis is a source of uncertainty and organizational change (Hewett & Lemon, 2019) because it occurs unexpectedly (Bundy et al, 2017;Coombs, 2007). Apart from that, a lack of frameworks combined with a lockdown situation in which communication between external stakeholders and decision-makers was limited resulted in a lack of creative innovation, indicating that the absence of foundations during a crisis can have significant consequences (Breier et al, 2021;Pinzaru et al, 2020;Saraceno, 2021;Vasickova, 2020).…”
Section: Brand Performancementioning
confidence: 99%
“…This leads to the importance of a brand in the survival and sustainability of a business. There is some evidence from the COVID-19 crisis that suggests hotel managers must build and maintain a strong brand, for which they must employ appropriate strategies and techniques and maintain a connection between the consumer and the brand (Hewett & Lemon, 2019;Lombardi et al, 2021;Nawaz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Like most services, financial services are intangible, but they are frequently complex and, moreover, fall into the category of utilitarian products, that is those that are necessary but spark little enthusiasm (Farquhar and Meidan, 2010). Marketing in financial services continues to stimulate research with studies into branding and trust (Moin and McKechnie, 2016), consumer-based brand equity (Pinar et al , 2016) and the role of marketing communications in response to brand crises (Hewett and Lemon, 2019). There has been limited enthusiasm for the role of stakeholders in financial services marketing, with some notable exception being Akamavi's (2005) study into new service development.…”
Section: Literature Reviewmentioning
confidence: 99%